Media Pembelajaran Berbasis Loose Parts Dan Peranan Orang Tua Dalam Memotivasi Semangat Belajar Pada Anak - Nur Habibah; Siti Mufarochah (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
The COVID-19 pandemic, which has not yet ended in Indonesia, has had an unfavorable impact on various fronts, one of which is the world of education. Education units are forced to carry out online learning. Parental support is needed so that the learning process continues optimally and children's interest in learning remains high. With the use of Loose Parts-based media, children are expected to remain creative and enthusiastic while studying at home, then parents are expected to be able to understand and facilitate the media used by children during the pandemic. The purpose of this study was to determine the effectiveness of the Loose Parts-based media approach to increase children's enthusiasm and creativity during the COVID-19 pandemic. This study uses a literature review method by collecting data and phenomena from the best sources. The results of this study indicate that the use of Loose Parts-based media is effective in increasing children's creativity and enthusiasm for learning from home during the COVID-19 pandemic.